2012
DOI: 10.1007/s00018-012-1194-z
|View full text |Cite
|
Sign up to set email alerts
|

LOX-1 in atherosclerosis: biological functions and pharmacological modifiers

Abstract: Lectin-like oxidized LDL (oxLDL) receptor-1 (LOX-1, also known as OLR-1), is a class E scavenger receptor that mediates the uptake of oxLDL by vascular cells. LOX-1 is involved in endothelial dysfunction, monocyte adhesion, the proliferation, migration, and apoptosis of smooth muscle cells, foam cell formation, platelet activation, as well as plaque instability; all of these events are critical in the pathogenesis of atherosclerosis. These LOX-1-dependent biological processes contribute to plaque instability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
207
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 250 publications
(227 citation statements)
references
References 112 publications
7
207
0
6
Order By: Relevance
“…LOX1 not only internalises modified lipids but also causes endothelial dysfunction, apoptosis, inflammation and smooth muscle cell proliferation, contributing to the process of atheroma formation at multiple levels (Xu et al 2013). LOX1 has been identified as the main endothelial receptor for oxLDL (Sawamura et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…LOX1 not only internalises modified lipids but also causes endothelial dysfunction, apoptosis, inflammation and smooth muscle cell proliferation, contributing to the process of atheroma formation at multiple levels (Xu et al 2013). LOX1 has been identified as the main endothelial receptor for oxLDL (Sawamura et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ox-LDL, these ligands include activated platelets, apoptotic bodies, bacteria, advanced glycation end products (AGEs), heat shock proteins (HSP60 and HSP70) and C-reactive protein (CRP) [62,68,70]. Beside endothelial cells, LOX-1 is expressed in several cell types including smooth muscle cells, fibroblasts and platelets [16,46,69].…”
Section: S Raniolo Et Al / Cholesterol Level Regulates Lectin-likementioning
confidence: 99%
“…Under physiological conditions, basal cellular LOX-1 expression is low in most tissues, while it is up-regulated in several pathophysiological processes such as inflammation, atherosclerosis, obesity and diabetes [59,68]. In this context, LOX-1 and ox-LDL contribute to plaque rupture in atherosclerosis by promoting lipid accumulation, oxidative stress, pro-inflammatory response, release of metalloproteinases and apoptotic cell death.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical structure of TSN and CPT are illustrated in Figure 1. Over the past decade, we [1,[10][11][12][13][14][15][16][17][18][19] and others [20][21][22][23][24] have demonstrated that TSN has potential protective effects against atherosclerosis, cardiac hypertrophy, cardiac fibrosis, diabetes, neurodegenerative diseases, and various kinds of cancers. However, the poor water-solubility, poor intestinal absorption, and low oral bioavailability (about 2.9 --3.4% in rats) [25] have hampered the clinical application of TSN.…”
Section: Tanshinone Ii-amentioning
confidence: 99%